Software-Infrastruktur. Von analytischer Perspektive zu konstruktiver Orientierung - Bleek, Wolf G. (Hamburg University Press, 2003)
The term "infrastructure" is used here for information systems. Software applications are related to other software and consist of software of different origins. In their networking, software is under the limited influence of different actors. Nowadays, software development is mainly concerned with further development, parameterization and configuration. Software infrastructure development must therefore deal with existing software and be carried out in complex contexts, taking into account a sharply increased number of interests and opportunities for interaction. Interference is recognized as a particular problem in infrastructure development. The proposed interference management addresses this. The core point of the extended evolutionary software development process is the continuous development of the relevant components and actors of the infrastructure against the background of our own development project, taking into account the various interests.